Children of Depressed Parents: Mechanisms of Risk and Implications for Treatment. 2002
DOI: 10.1037/10449-008
|View full text |Cite
|
Sign up to set email alerts
|

Family context: Fathers and other supports.

Abstract: Although there is a wealth of information regarding the children of mothers who are depressed, there is far less information about the children of fathers who are depressed (Kaslow, Deering, & Racusin, 1994). Possible reasons for this lack of research on depressed fathers include the greater prevalence of major depression in women than in men, the possibility that fathers are more difficult than mothers to recruit into research, the greater research attention to maternal as opposed to paternal parenting proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 85 publications
1
25
0
3
Order By: Relevance
“…This lack of structure creates a fragile family system. This is evident as families with a depressed parent are less likely to adapt to new or compounding stresses than those without (Phares et al, 2002).…”
Section: Effects Of Paternal Depression Upon the Familymentioning
confidence: 93%
See 2 more Smart Citations
“…This lack of structure creates a fragile family system. This is evident as families with a depressed parent are less likely to adapt to new or compounding stresses than those without (Phares et al, 2002).…”
Section: Effects Of Paternal Depression Upon the Familymentioning
confidence: 93%
“…Children and adolescents of depressed parents, mother or father, demonstrate more emotional and behavioral problems or suffer from major depression more often than those without (Jacob & Johnson, 2001;Shiner & Marmorstein, 1998). Children of a depressed parent exhibit lower intellectual functioning, difficult temperaments, and lower social-cognitive ability (Phares et al, 2002). Moreover, risk of psychopathology in children of depressed fathers is comparable to the risk associated with depressed mothers (Phares & Compas, 1993).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…When one parent is depressed, the other parent may attempt to compensate for the impaired functioning of the depressed parent, 14,20 possibly resulting in better parenting practices Log of the (internalizing -84) or (externalizing -81) problem behavior level at age 4 years for a white female child with no father's involvement in her life, who does not live with either the biological father or the stepfather and lives in a rural area, and has a nondepressed mother whose educational level, number of children in the household, and age at childbirth are average relative to other mothers in the study sample. in the home environment.…”
Section: Commentmentioning
confidence: 99%
“…They further suggest that a 'psychosocial family disturbance' associated with mother's PPD represents a greater risk to child development than mother's PPD alone. Phares, Duhig, and Watkins (2002) also reported that marital relationship quality is a better predictor of child's outcome than mother's depression. However, it is not clear which is the causal determinant of the association between PPD and marital conflict.…”
Section: Marital and Co-parental Relationship And Ppdmentioning
confidence: 94%